Identification of common factors of innovation in a SMME - Rautela, Nikhil (Graduate School of Business (GSB), 2019)
Small, Medium and Micro Enterprise (SMME) businesses in manufacturing contribute significantly to the economic growth of a nation, yet most of the research on innovation management in manufacturing industries has been focused on big firms. The current study identifies factors in SMME’s that are common between the external and internal systems of innovation that supports firms in their management of innovation. The study gathered data through qualitative and quantitative interviews of 20 companies out of which 5 manufacturing firms in Western Cape, South Africa selected for this research. The study found that SMMEs acquire new knowledge from the external ecosystem to supplement their limited internal system based on the product or process development. This study identifies the common factors that the SMMEs can use as a guiding framework to pursue new innovative opportunities for development of product or process.